2006
DOI: 10.1111/j.1600-0501.2005.01169.x
|View full text |Cite
|
Sign up to set email alerts
|

Implant–tooth‐supported fixed partial prostheses: correlations between in vivo occlusal bite forces and marginal bone reactions

Abstract: Although MOFs under functional loading might indicate an increase in load participation for supporting implant, the rigid connection between implant and natural tooth via three-occlusal unit FPP does not jeopardize the time-dependent MBL stability of the implant under functional loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 28 publications
1
34
0
4
Order By: Relevance
“…Short-term clinical success in tooth-implant-supported and implant-supported prosthesis is similar. As a result of the 24-month followup, there was no resorption in the level of marginal bone of implants despite the load increase on the implant [22].…”
Section: Bone Lossmentioning
confidence: 92%
See 1 more Smart Citation
“…Short-term clinical success in tooth-implant-supported and implant-supported prosthesis is similar. As a result of the 24-month followup, there was no resorption in the level of marginal bone of implants despite the load increase on the implant [22].…”
Section: Bone Lossmentioning
confidence: 92%
“…For this reason, �exibility of implant, tooth, and bone should be similar for distrubiting stresses equally and it was emphasized that periodontal ligaments of existing teeth have to be healthy when planning teeth-implant supported prosthesis. Akça et al (2006) [22], concluded that marginal bone surface resorption amount is negligible in rigid connection of �xed prosthesis. ere are lots of researches to refer and describe rigid implant-tooth connection in the current literature [12,23].…”
Section: Bone Lossmentioning
confidence: 99%
“…The results showed no significant differences in functional load magnitudes related to the abutment type. Akca et al 35 performed a similar study (in vivo) to evaluate maximal occlusal bite forces (MOFs) and marginal bone level changes in patients with tooth-implant-supported FPPs. They came to the conclusion that even MOFs under functional loading were higher for implants (mean: 353,61N) than for teeth (mean: 275,48N).…”
Section: Methodsmentioning
confidence: 99%
“…Several authors advocate the use of a rigid connection 25,28,35,38,39 , which assumes a stiff junction between component parts of the structure with no relative motion of one part against another. The use of this type of connector reduces tooth intrusion incidence and transfers the load Meniccuci et al 28 implemented 2D and 3D FEAs to assess the stress in the bone around an implant and a tooth which are rigidly connected when a load is applied on the tooth.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in union between an osseointegrated implant and a natural tooth's union to the alveolar bone through periodontal ligament fibers mean that they behave very differently in response to the different masticatory forces, both natural and pathological. A number of published studies and articles have dealt with this issue in very different ways: bibliographic reviews (1,2); in vivo studies (3,4); in vitro biomechanical studies (5)(6)(7) and clinical case studies (8). The aim of the present study was to conduct a bibliographic review of all the above literature published since the year 2000, to examine the connection of natural teeth to dental implants by means of tooth-to-implant supported prostheses and by doing so to determine if tooth-implant connection is a viable treatment option or not and, if so, in which cases might it be an appropriate option.…”
Section: Introductionmentioning
confidence: 99%